How can we help children adopt healthy sun protection habits? A quasi-experiment using Internet of Things (IoT), gamification, and a social mission. - Θεοδόση, Σωτηρούλα; Nicolaidou, Iolie (My University, 2025)
The preventability of skin cancer stresses the need for primary prevention interventions early in life to help children realize how dangerous ultraviolet radiation (UVR) exposure can be. Internet of Things (IoT) devices can be used to measure UVR intensity in real-time to help children visualize it and understand the need for sun protection from an early age when behaviors are receptive to change. The present study implements a data-driven approach using IoT, gamification, and a social mission to affect elementary school children’s sun-related knowledge, habits, and behavioral change, respectively. The research questions examine the IoT’s effect on 10–11 year-old students’ knowledge of UVR, the gamification’s effect on habits and behaviors, and the social mission’s effect on behavioral change regarding sun protection measures. A quasi-experimental design was used with 53 students (33 in the experimental group and 20 in the control group). Data sources included a content knowledge test on UVR and the validated questionnaire “Sun Exposure and Protection Index” (SEPI) administered pre and post. Findings demonstrated significant learning gains for experimental group participants that were preserved five weeks post-intervention, indicating the effectiveness of IoT as a learning technology. Moreover, the experimental group students’ sun exposure habits and behaviors post-intervention were slightly but significantly improved, indicating that gamification as a pedagogical strategy was effective. Lastly, a positive but not significant propensity to change sun protective behaviors was observed in the experimental group, indicating that the social mission was not as effective as other components of the intervention. A challenge that remains unsolved is, therefore, how to positively affect children’s behavioral change regarding sun-protection measures.
Keywords: Internet of Things (IoT); Prevention interventions; Children; Behavioral change; Sun protection; Ultraviolet raditation